2019
DOI: 10.1016/j.brs.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the cardiovascular response during single-pulse TMS in perinatal stroke

Abstract: Serious adverse events of syncope have been reported with single pulse transcranial magnetic stimulation (sp-TMS) in both healthy adults and adolescents post stroke [3,5,[7][8][9]. Despite these reports, the physiological mechanisms leading to syncope during sp-TMS administration are not clearly understood. A syncopal event is classically identified by a sudden, large reduction in blood supply to neural tissue "cerebral hypoperfusion" to ultimately cause a loss of consciousness [2]. Common symptoms preceding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Based on previous reports of syncope from sp-TMS ( Gillick et al, 2015 ), it may appear that active sp-TMS decreases BP. The lack of reductions in BP and HR with sp-TMS in our study is consistent with our previous work in children with cerebral palsy ( Keller-Ross et al, 2018 ). Although, sp-TMS has been shown to inhibit sympathetic activity ( Macefield et al, 1998 ), which would likely decrease BP, Macefield et al (1998) observed nonsignificant increases in diastolic BP.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…Based on previous reports of syncope from sp-TMS ( Gillick et al, 2015 ), it may appear that active sp-TMS decreases BP. The lack of reductions in BP and HR with sp-TMS in our study is consistent with our previous work in children with cerebral palsy ( Keller-Ross et al, 2018 ). Although, sp-TMS has been shown to inhibit sympathetic activity ( Macefield et al, 1998 ), which would likely decrease BP, Macefield et al (1998) observed nonsignificant increases in diastolic BP.…”
supporting
confidence: 93%
“…In both the previous study and the current study, these individuals had relatively stable vitals during experimental sessions indicating that the near-syncopal event was not due to direct physiological responses to cortical stimulation. Although the novel stimulus was less likely the case in our previous report ( Keller-Ross et al, 2018 ), it may be a likely cause in the current study as it occurred during initial TMS testing.…”
mentioning
confidence: 58%
See 3 more Smart Citations